REKONSTRUKSI WASIAT WAJIBAH KELUARGA MULTIRELIGIUS : Sebagai Instrumen Perlindungan Hak Keluarga - Nur Afifa Maharani; Hesti Rahma; Tasliyah Erlina Ramli; Azman Arsyad; Andi Herawati (MAQASHID, 2026)
Religious difference (ikhtilāf al-dīn) bars non-Muslim family members from inheritance under Islamic law, yet Indonesian Supreme Court jurisprudence has expanded mandatory bequests to protect multireligious families. The Compilation of Islamic Law, however, does not explicitly regulate this expansion, producing legal uncertainty and inconsistent judicial decisions. This study uses normative legal research with statutory, conceptual, and case approaches. It examines legislation, four Supreme Court decisions, Islamic legal literature, and maqāṣid al-syarī'ah theory to formulate a reconstruction of mandatory bequests as an instrument of legal protection. The reconstruction comprises three components: expanding recipients to non-Muslim family members with lawful blood or marital ties to the deceased, establishing operational normative parameters, and harmonizing Supreme Court jurisprudence with the Compilation of Islamic Law. Situated within the maqāṣid hierarchy of ḍarūriyyāt, ḥājiyyāt, and taḥsīniyyāt, the reconstruction preserves religious difference as an impediment to inheritance while strengthening legal certainty, justice, and public benefit for multireligious families.